How time consuming are general practitioners’ home visits? Insights from a cross-sectional study in Switzerland (Swiss Medical Weekly, 2023)
BACKGROUND: Worldwide, the number of home visits has been decreasing over past decades. Lack of time and long journeys have been reported to hinder general practitioners (GPs) from conducting home visits. In Switzerland also, home visits have declined. Time constraints in a busy GP practice could be one reason. Therefore, the aim of this study was to analyse the time requirements of home visits in Switzerland.METHODS: A one-year cross-sectional study involving GPs from the Swiss Sentinel Surveillance System (Sentinella) was conducted in 2019. GPs provided basic information on all home visits performed throughout the year and additionally detailed reports of up to 20 consecutive home visits. Univariable and multivariable logistic regression analyses were run to identify factors affecting journey and consultation duration.RESULTS: In total, 95 GPs conducted 8489 home visits in Switzerland, 1139 of which have been characterised in detail. On average, GPs made 3.4 home visits per week. Average journey and consultation duration were 11.8 and 23.9 minutes, respectively. Prolonged consultations were provided by GPs working part-time (25.1 minutes), in group practice (24.9 minutes) or in urban regions (24.7 minutes). Rural environments and short journey to patient’s home were both found to lower the odds of performing a long consultation compared to a short consultation (odds ratio [OR] 0.27, 95% confidence interval [CI] 0.16–0.44 and OR 0.60, 95% CI 0.46–0.77, respectively). Emergency visits (OR 2.20, 95% CI 1.21–4.01), out-of-hours appointments (OR 3.06, 95% CI 2.36–3.97) and day care involvement (OR 2.78, 95% CI 2.13–3.62) increased the odds of having a long consultation. Finally, patients in their 60s had markedly higher odds of receiving long consultations than patients in their 90s (OR 4.13, 95% CI 2.27–7.62), whereas lack of chronic conditions lowered the odds of a long consultation (OR 0.09, 95% CI 0.00–0.43).CONCLUSION: GPs perform rather few but long home visits, especially for multimorbid patients. GPs working part-time, in group practice or in urban regions devote more time to home visits.